2006
DOI: 10.1182/blood-2005-05-1902
|View full text |Cite
|
Sign up to set email alerts
|

The intracellular domain of CD44 promotes the fusion of macrophages

Abstract: Macrophages seed all tissues in which they have the ability, in specific and rare instances, to fuse with themselves and to differentiate into osteoclasts in bone or into giant cells in chronic inflammatory reactions. Although these cells play a central role in osteoporosis and in foreign body rejection, respectively, the molecular mechanism used by macrophages to fuse remains poorly understood. Macrophages might also fuse with somatic and tumor cells to promote tissue repair and metastasis, respectively. We r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
82
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(82 citation statements)
references
References 56 publications
0
82
0
Order By: Relevance
“…(13) Therefore, although the functions of osteoclasts and FBGCs differ, they express common molecules, such as DC-STAMP, that function in cell-cell fusion. (3) To date, various molecules have been identified that regulate fusion of osteoclasts or macrophages, including DC-STAMP, ATP6v0d2, CD47, CD44, CD9, CD81, MFR, E-cadherin, and meltrin-a (3,(14)(15)(16)(17)(18)(19)(20)(21) ATP6v0d2-deficient mice show significant reductions in fusion of either cell type. (21) DC-STAMP-deficient osteoclasts or FBGCs show a complete lack of cell-cell fusion, a function specific for macrophage lineage fusion, since fertilization and myotube formation is normal in DC-STAMP-deficient mice.…”
Section: Introductionmentioning
confidence: 99%
“…(13) Therefore, although the functions of osteoclasts and FBGCs differ, they express common molecules, such as DC-STAMP, that function in cell-cell fusion. (3) To date, various molecules have been identified that regulate fusion of osteoclasts or macrophages, including DC-STAMP, ATP6v0d2, CD47, CD44, CD9, CD81, MFR, E-cadherin, and meltrin-a (3,(14)(15)(16)(17)(18)(19)(20)(21) ATP6v0d2-deficient mice show significant reductions in fusion of either cell type. (21) DC-STAMP-deficient osteoclasts or FBGCs show a complete lack of cell-cell fusion, a function specific for macrophage lineage fusion, since fertilization and myotube formation is normal in DC-STAMP-deficient mice.…”
Section: Introductionmentioning
confidence: 99%
“…BMMs were isolated and cultured as per the protocol of Cui et al 29 Mouse bone marrow cells were flushed from the femurs of 8-to 12-week-old mice and passed through a 40-m cell strainer (BD Falcon), and red blood cells were lysed in ACK buffer (0.15 M NH 4 Cl, 10 mM KHCO 3 , 0.1 mM EDTA). Remaining cells were incubated in MEM␣ medium (Life Technologies) containing 10% FBS (Sigma), 10% L929 fibroblast cell supernatant (generously provided by Dr. Agnes Vignery), 1% glutamine (Life Technologies), 1% MEM vitamin (Life Technologies), and 1% penicillin/streptomycin (Life Technologies).…”
Section: Isolation and In Vitro Polarization Of Mononuclear Phagocytesmentioning
confidence: 99%
“…Macrophage fusion receptor (MFR; also called SHPS-1), a member of immunoglobulin (Ig) superfamily, was shown to function in macrophage cell-cell fusion based on loss-of-function assays using MFR monoclonal antibodies or the soluble form of the extracellular domain of MFR (7,8). CD47, an MFR ligand, and the intracellular domain of CD44 (CD44ICD) have also been implicated in macrophage cell-cell fusion (9,10). DAP12, an ITAM motif-containing adaptor protein, and the signaling molecule Syk were also reportedly involved in cell-cell fusion of macrophages (11).…”
mentioning
confidence: 99%